An analysis on natural fiber composite materials. (2021) - Ramakrishna, Ganga; Kiran babu, P.; Purushothaman, K.; Sivakumar, E.R.; Sreenivasan, M.
Abstract: This experimental research is intended to study the mechanical functioning of natural hybrid particulate fiber composites. The fiber and matrix fraction is held at varying percentages and the samples are produced by hand from several specific cocoa coats, soil nuts, walnut coats, and rice husk fiber. For different tensile tests and bending test samples in the flat bar, all steps shall be held in compliance with the requirements of ASTM. Composite materials have many benefits over traditional engineering materials. It can be used to replace various traditional materials in automobiles because of the enormous use. Currently, if a vehicle has mechanical features of traditional steel, the integrated composite material substitutes the framework and axis.